MEMBIMBING DAN MENGENALKAN ROH KUDUS KEPADA ANAK BROKEN HOME - Anis Anis; Kristina Pither; Dwi Megawati (JIP: Jurnal Ilmu Pendidikan, 2023)
The title of this journal is "Guiding and Introducing the Holy Spirit to broken home children". The author of this journal is expected to answer the problem formulation regarding how to guide broken home children under the guidance of the Holy Spirit. Based on the problems mentioned above, the authors of this journal set a goal so that we can find out how to find children who experience a broken home under the guidance of the Holy Spirit. And it is more directed to parents who only care about themselves and only care about their ego. In Proverbs 22:6, God gives directions to parents to educate their children. The role of parents in Proverbs 22:6 is to nurture, train, guide and direct, with the aim that children become successful people in their lives, and do not deviate from the teachings of their parents. The method used in writing this journal is the library method. After explaining the theory related to the problem, it can be concluded that the Holy Spirit is a real person who came to live in a true follower of Christ after Jesus rose from the dead and reigned in heaven.